Connective tissue graft vs. emdogain: A new approach to compare the outcomes - Ferena Sayar; Nasrin Akhundi; Sanaz Gholami (Wolters Kluwer Medknow Publications, 2013)
Background: The aim of this clinical trial study was to clinically evaluate the use of enamel matrix protein derivative combined with the coronally positioned flap to treat gingival recession compared to the subepithelial connective tissue graft by a new method to obtain denuded root surface area. Materials and Methods: Thirteen patients, each with two or more similar bilateral Miller class I or II gingival recession (40 recessions) were randomly assigned to the test (enamel matrix protein derivative + coronally positioned flap) or control group (subepithelial connective tissue graft). Recession depth, width, probing depth, keratinized gingival, and plaque index were recorded at baseline and at one, three, and six months after treatment. A stent was used to measure the denuded root surface area at each examination session. Results were analyzed using Kolmogorov-Smirnov, Wilcoxon, Friedman, paired-sample t test. Results: The average percentages of root coverage for control and test groups were 63.3% and 55%, respectively. Both groups showed significant keratinized gingival increase ( P < 0.05). Recession depth decreased significantly in both groups. Root surface area was improved significantly from baseline with no significant difference between the two study groups ( P > 0.05). The results of Friedman test were significant for clinical indices ( P < 0.05), except for probing depth in control group ( P = 0.166). Conclusion: Enamel matrix protein derivative showed the same results as subepithelial connective tissue graft with relatively easy procedure to perform and low patient morbidity.